RUANG KOMUNITAS ANAK JALANAN DI GROGOL, JAKARTA BARAT - Wijaya, Janice Adriana; Carina, Nina (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2024)
Children are the nation's next generation who are expected to realize positive hopes in the future. Until now, the phenomenon of street children is still a social problem that is often found in big cities in Indonesia, one of which is Jakarta. Street children is a term for children aged 6 to 18 years who spend most of their time on the street to survive by earning income, either in the form of money or goods. Grogol Petamburan, as an administrative area in West Jakarta, is one of the locations with the most social welfare problems. Environment is a crucial factors that influences children's health physically, psychologically and socially. The streets in Grogol, with high vehicle intensity and unhealthy air quality have the potential to hinder the growth and development process of children. The majority of street children in Grogol have the same enthusiasm for learning as other children. However, they have little opportunity to pursue non-formal education outside of school. Based on research, they have special behavior in learning, which also influences their activity space. Therefore, a community space is needed that can improve the quality of life of street children. Through empathetic architecture, community space is realized through productive activities in the form of training, teaching and socialization. The space-forming elements that are created must be based on the behavioral patterns of street children in order to create a comfortable place for street children as the main users. Keywords:  activity; behavior; children; environmen; street Abstrak Anak merupakan generasi penerus bangsa yang diharapkan mampu mewujudkan harapan positif di masa yang akan datang. Hingga saat ini, fenomena anak jalanan masih menjadi masalah sosial yang banyak ditemui di kota-kota besar di Indonesia, salah satunya Jakarta. Anak jalanan merupakan sebuah istilah untuk anak-anak berusia 6 hingga 18 tahun yang menghabiskan sebagian besar waktunya di jalan untuk bertahan hidup dengan memperoleh pemasukan, baik dalam bentuk uang ataupun barang. Grogol Petamburan sebagai wilayah administratif di Jakarta Barat, menjadi salah satu lokasi dengan penyandang masalah kesejahteraan sosial terbanyak. Lingkungan merupakan salah satu faktor krusial yang mempengaruhi kesehatan anak secara fisik, psikologi, maupun sosial. Jalanan di Grogol, dengan intensitas kendaraan yang tinggi dan kualitas udara dalam kategori tidak sehat berpotensi menghambat proses tumbuh kembang pada anak. Mayoritas anak jalanan di Grogol memiliki semangat belajar yang sama dengan anak-anak lainnya. Hanya saja, kecil kesempatan mereka untuk menempuh pendidikan non-formal di luar sekolah. Setelah diteliti, anak jalanan memiliki perilaku khusus dalam belajar, yang turut mempengaruhi ruang aktivitas mereka. Oleh karena itu, diperlukan ruang komunitas untuk meningkatkan kualitas hidup anak jalanan. Melalui arsitektur yang berempati, ruang komunitas diwujudkan melalui aktivitas produktif berupa pelatihan, pengajaran, dan sosialisasi. Elemen pembentuk ruang yang diwujudkan harus didasari oleh pola perilaku anak-anak jalanan agar sesuai dan nyaman bagi anak jalanan selaku pengguna utama.